2022
DOI: 10.1111/ajt.16956
|View full text |Cite
|
Sign up to set email alerts
|

Successful kidney transplantation from a deceased donor with severe COVID-19 respiratory illness with undetectable SARS-CoV-2 in donor kidney and aorta

Abstract: Kidney transplantation (KT) from coronavirus disease 2019 (COVID-19) donors were avoided due to concerns for donor-derived transmission. 1,2 There have been no data on the long-term safety,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…One of the primary findings from the study was that recipient outcomes with use of SARS‐CoV‐2–positive donor organs are similar to outcomes with negative testing. These data complement prior smaller single‐center reports and case series and may provide assurance that, at least short‐term outcomes are not compromised by use of these organs 7–11,13,20,21 . In the context of kidney transplantation, the current study indicated no difference in rates of delayed graft function or 6‐month graft survival and the characteristics of recipients was similar between negative and positive SARS‐CoV‐2 status donors.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…One of the primary findings from the study was that recipient outcomes with use of SARS‐CoV‐2–positive donor organs are similar to outcomes with negative testing. These data complement prior smaller single‐center reports and case series and may provide assurance that, at least short‐term outcomes are not compromised by use of these organs 7–11,13,20,21 . In the context of kidney transplantation, the current study indicated no difference in rates of delayed graft function or 6‐month graft survival and the characteristics of recipients was similar between negative and positive SARS‐CoV‐2 status donors.…”
Section: Discussionsupporting
confidence: 79%
“…These data complement prior smaller single‐center reports and case series and may provide assurance that, at least short‐term outcomes are not compromised by use of these organs. 7 , 8 , 9 , 10 , 11 , 13 , 20 , 21 In the context of kidney transplantation, the current study indicated no difference in rates of delayed graft function or 6‐month graft survival and the characteristics of recipients was similar between negative and positive SARS‐CoV‐2 status donors. Similarly for liver and transplant recipients, both general characteristics of recipients and 6‐month graft survival were similar by SARS‐CoV‐2 status donors.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…provided the first hints that SARS-CoV-2 infection in kidney organoids is amenable to a treatment with a protease inhibitor, providing a glimpse into potential future treatments for COVID-19-related kidney injury. The findings also stimulate further clinical and translational investigations for testing SARS-CoV-2 tropism in the kidneys of infected individuals to identify potential virus-free kidneys for transplantation procured from individuals who died of fulminant COVID-19 ( Lee et al., 2022 ).…”
Section: Main Textmentioning
confidence: 83%